Kinetics of Pulmonary Ventilation and Carbon Dioxide Output during Intermittent Increasing Cycling Exercise after a Prior Anaerobic Load (Baltic Journal of Sport and Health Sciences, 2014)
Background. Research aim was to establish the influence of a prior anaerobic load on the kinetics of ventilation (V E )  and  carbon  dioxide  output  (VCO 2 )  during  on-  and  off-transition  phases  of  intermittent  increasing  cycling exercise.Methods. The seven healthy, physically active females volunteered to estimate the influence of a prior anaerobic load on the kinetics of respiratory parameters. During the first visit VO 2 max was evaluated using the increasing cycling  exercise  test.  During  the  second  testing  the  participants  performed  intermittent  cycling  exercise  (ICE). During the other visit they performed supramaximal 30 s anaerobic exercise and after 15 min of the rest – ICE. In order to estimate the kinetics of respiratory parameters were analysed by adopting mono-exponential function. Results. Mean blood lactate concentration was increased during ICE performed after prior anaerobic load in the presence of a residual metabolic acidosis. The asymptote and amplitude of monoexponential function reflecting VCO 2  kinetics during on- and off-transitions were not changed after prior anaerobic load. The time constant of this function was significantly longer (p  < .01) both during on- and off-transitions at work rate below lactate threshold (LT), whereas this parameter at higher work intensities remained unchanged. The parameters of V E  monoexponential function during on- and off-transitions were not changed after prior anaerobic load.Conclusion. Despite similar physiological mechanism responsible for V E  and CO 2  regulation during exercise the prior anaerobic load had different influence on the ventilation and VCO 2  kinetics during exercise below lactate threshold causing slowing of VCO 2  without changes of V E  kinetics.Keywords: exercise intensity, lactate threshold, pulmonary ventilation, CO2 output, acidosis.